Pengaruh Kebijakan Logistik Terhadap Efisiensi Inventori di TNI AL - Sudarwanto, Dwi; Riesnandar, Edi; Indarto, Yogi; Nurhartonosuro, Imam Munajat (Universitas Pahlawan Tuanku Tambusai, 2024)
Inventory efficiency is a crucial factor in logistics management which has a direct impact on the company's operational and financial performance. Implementation of appropriate logistics policies, such as Just-In-Time (JIT), Vendor-Managed Inventory (VMI), and Economic Order Quantity (EOQ), can significantly influence inventory management efficiency. This research aims to analyze the influence of logistics policies on inventory efficiency in the company environment. The main focus is to identify the relationship between logistics policy implementation and inventory efficiency as well as to evaluate the factors that influence inventory performance in companies. This research uses a quantitative approach using a survey of 40 respondents who are personnel related to logistics management in companies. Data collection was carried out through a questionnaire designed to measure perceptions of the effectiveness of logistics policies and inventory efficiency. Data analysis was carried out using descriptive statistics, Cronbach's alpha reliability test, simple linear regression, and F significance test. The results of the analysis show that logistics policies such as JIT, VMI, and EOQ have a significant positive correlation with inventory efficiency. The regression coefficient between Logistics Policy and Inventory Efficiency is 0.739, with a very low statistical significance value (p = 0.000), indicating the strong influence of logistics policy on inventory performance. The reliability test results show a high level of confidence in the measurement instruments used in this research.